O "Timed Up and Go" na previsão e explicação de quedas em idosos praticantes de exercícios físicos - Janeisa Franck Virtuoso; Luis Paulo Perdona Gregório; Paulo Adão de Medeiros; Giovana Zarpellon Mazo (Universidade Federal de Santa Catarina, 2014)
The classic and cognitive "Timed Up and Go" tests (TUG) are used to identify old people prone to falls, but we were unable to find studies that prove their association in old people practicing physical exercise. The objective of this study was to analyze the classic and cognitive versions of TUG in forecasting and explaining the occurrence of falls in old people practicing physical exercise. Participants included 82 physically active old people. Data were collected on the occurrence of falls in the past 12 months among those who performed the classic and the cognitive TUG tests through the pronunciation of animals while performing the test. We used descriptive and inferential statistics with a significance level of 5%. A binary logistic regression was performed to associate the outcome (falls) and the performance in the tests. To identify the predictive values, the ROC Curve was used. The occurrence of falls in the sample was 19.5%. There was a significant difference between the values obtained in the TUG classic and cognitive tests (9.0 ± 1.9 and 10.0 ± 2.2 seconds, respectively). There was no difference between the old people with and without a history of falls in both tests, despite the averages being higher in old people with a history. In the logistic regression analysis, the performance of both versions did not explain the occurrence of falls. In the ROC curve, the TUG classic test showed an accuracy of 65.3% (p= 0.058) and the TUG cognitive test of 58.1% (p= 0.324). The TUG classic and cognitive tests did not correlate with the occurrence of falls and should be used with caution for predicting falls in old people practicing physical exercise.